FOLLOW-UP (CIPEEX, 2024)
Follow Up business rules include the management of registrations and permissions for schools, educators, and parents, the recording and evaluation of student behavior, direct communication via chat with stored history, and the sending of notifications about school events, deadlines, grades, and behaviors. Additionally, success metrics are monitored, such as the number of registered users, the frequency of app use, and the level of engagement in the chat, aiming to ensure that Follow Up meets the needs of the school community and promotes a more collaborative and effective learning environment.
Keywords: school communication; parent engagement; student monitoring; educational app